2018
DOI: 10.1016/j.jvs.2017.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of delayed wound healing after successful isolated below-the-knee endovascular intervention in patients with ischemic foot ulcers

Abstract: The general status of the patient and the target limb's condition are important predictors of wound nonhealing. Regarding the limb's condition, information on wound depth and duration in addition to wound extent and infection would further enable the selection of suitable CLI patients for EVT. Such information would also enable optimal wound management, leading to successful wound healing and improved limb salvage and survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…We identified 28 cohorts from 21 studies (in 23 publications) for inclusion in the review; together these report data on 38,604 participants. 4,6,13,17,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Some studies reported on more than one cohort (cohorts with different wound aetiologies or RCT treatment groups analysed as cohorts). These studies were identified from screening of 913 records following deduplication of the searches; we identified a further six studies from reference checking and assessed 272 studies as full text.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 28 cohorts from 21 studies (in 23 publications) for inclusion in the review; together these report data on 38,604 participants. 4,6,13,17,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Some studies reported on more than one cohort (cohorts with different wound aetiologies or RCT treatment groups analysed as cohorts). These studies were identified from screening of 913 records following deduplication of the searches; we identified a further six studies from reference checking and assessed 272 studies as full text.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two of the 28 cohorts included participants whose wounds had mixed infection status at baseline (some participants had infected wounds at baseline and some had non-infected wounds). 4,6,[31][32][33][34][35][36][37][38][39][40][41][42][43] This represents the overwhelming majority of participants (Figure 2(B)). Most cohorts of participants with mixed infection status wounds assessed the role of clinical infection (variously defined) as a prognostic factor for healing (Figure 3).…”
Section: Characteristics Of Cohortsmentioning
confidence: 99%
“…16 In the current study, plasma levels of NAP-2 were independently associated with CLI, but were not associated with T2DM. Diabetes delayed the healing of foot ulceration, 19,20 and CLI was the main causes for healing of lower limbs ulcers; 21,22 therefore, plasma NAP-2 levels not only may be a biomarker to predict the lower limb ischemia in the non-diabetic CLI population, but they also may be an ideal marker to predict the wound healing in diabetic CLI population.…”
Section: Discussionmentioning
confidence: 99%
“…A new analysis and review made by Das et al [83] in a 422 consecutive series of CLI patients, all treated by AC first-option strategy shows that beyond correct topographic foot flow reconstruction, the depths of ulcers, their duration, the albumin and the C-reactive protein levels, also the presence of local infection and gangrene represent independent factors to be carefully pondered in statistic evaluation [83]. Similar findings were reported by Lo et al [84] in another 809 patients analysis a few months ago.…”
Section: Current Literature Review Concerning Dr/wtr Strategiesmentioning
confidence: 99%